Between Conservatization and Modernization of Human Rights: A Study of MU's Fatwa on Ahmadiyah - Zainul Mun'im (Asian Journal of Law and Humanity, 2022)
Indonesian Council of â€˜Ulama (MUI) has been issuing fatwas since its establishment in 1975. Among all the fatwas, there is the fatwa on Ahmadiyah group that aims to keep the orthodoxy of Sunni away from deviant theology. This study aims to examine the role of MUI in its fatwa on Ahmadiyah from the perspective of Islamic law and human rights. This research is qualitative research with a pattern of normative research through an in-depth study of the arguments of MUI. This fatwa on the Ahmadiyah group is based on two arguments. The first argument is Islamic law based on the Quran, hadith, and ijmaâ€™ concerning the exegesis and opinion of classical scholars. The second argument is the restrictions on human rights by arguing that the Ahmadiyah group can be a threat to public order. MUI assumes that every group or theology that is declared as â€œdeviantâ€ and incompatible with Quran, hadith, and ijmaâ€˜ is considered as a threat to public order. In other words, MUI still makes the classic literature as a reference for his fatwas, but at the same time, he tries to understand the public order as the principles of human rights. This position shows that MUI has a dual role, namely as the agent of modernization and conservatism in human rights discourse.